sqrt(8x+1)=sqrt(4x+9)

Simple and best practice solution for sqrt(8x+1)=sqrt(4x+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for sqrt(8x+1)=sqrt(4x+9) equation:


Simplifying
sqrt(8x + 1) = sqrt(4x + 9)

Reorder the terms:
qrst(1 + 8x) = sqrt(4x + 9)
(1 * qrst + 8x * qrst) = sqrt(4x + 9)
(1qrst + 8qrstx) = sqrt(4x + 9)

Reorder the terms:
1qrst + 8qrstx = qrst(9 + 4x)
1qrst + 8qrstx = (9 * qrst + 4x * qrst)
1qrst + 8qrstx = (9qrst + 4qrstx)

Solving
1qrst + 8qrstx = 9qrst + 4qrstx

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-9qrst' to each side of the equation.
1qrst + -9qrst + 8qrstx = 9qrst + -9qrst + 4qrstx

Combine like terms: 1qrst + -9qrst = -8qrst
-8qrst + 8qrstx = 9qrst + -9qrst + 4qrstx

Combine like terms: 9qrst + -9qrst = 0
-8qrst + 8qrstx = 0 + 4qrstx
-8qrst + 8qrstx = 4qrstx

Add '-4qrstx' to each side of the equation.
-8qrst + 8qrstx + -4qrstx = 4qrstx + -4qrstx

Combine like terms: 8qrstx + -4qrstx = 4qrstx
-8qrst + 4qrstx = 4qrstx + -4qrstx

Combine like terms: 4qrstx + -4qrstx = 0
-8qrst + 4qrstx = 0

Factor out the Greatest Common Factor (GCF), '4qrst'.
4qrst(-2 + x) = 0

Ignore the factor 4.

Subproblem 1

Set the factor 'qrst' equal to zero and attempt to solve: Simplifying qrst = 0 Solving qrst = 0 Move all terms containing q to the left, all other terms to the right. Simplifying qrst = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(-2 + x)' equal to zero and attempt to solve: Simplifying -2 + x = 0 Solving -2 + x = 0 Move all terms containing q to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + x = 0 + 2 x = 0 + 2 Combine like terms: 0 + 2 = 2 x = 2 Add '-1x' to each side of the equation. x + -1x = 2 + -1x Combine like terms: x + -1x = 0 0 = 2 + -1x Simplifying 0 = 2 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 0.8(4-g)=5.6g | | 6(-5n+1)+5n=-2n-40 | | 2x-(-2+x)=3 | | 10x+4x^2=66 | | 7/8p-r | | -(-5x+4)= | | -3x-5y=4 | | -y-15y-4y+13y+2y=20 | | -1(1-4x)=-22+x | | k^2+6+5k=0 | | 96-n=-23 | | 7q=9(q+4) | | 6-4x=-9x+8 | | 12+(-3)+(-1)= | | H=120t-16t^2 | | 1/4x-37.25=52.50 | | 8(-27)-11= | | y-8x=12 | | 2m-7=8+2m | | 2800=460+65m | | 2^20/2^3 | | 4=k/6 | | 4g-2g-g=10 | | -(1-4x)=22+x | | 2y-6x-12=0 | | 5/7x=40.5 | | 3m+-19=14 | | (y^2/3)^-9 | | 3m-19=24 | | 8*n=80 | | 6y+2x-y-x= | | .2/10 |

Equations solver categories